Climate change, agriculture, and adaptation options for Costa Rica - Sain, Gustavo; Thomas, Timothy S.; Cenacchi, Nicola (International Food Policy Research Institute, 2019)
This discussion paper evaluates the likely impact of climate change on agriculture in Costa Rica out to 2050. It includes an overview of the current state of the agricultural sector and presents projections for change that are driving both supply and demand in the food and agriculture sector. It finds that while Central America is likely to experience some of the largest yield losses in Latin America for important regional crops, Costa Rica is one of the lesser affected countries in the region. Nonetheless, climate change will have an important impact on its agricultural sector which cannot be ignored. Analysis in this discussion paper pointed to three commodities to monitor carefully: sugarcane, coffee, and dairy. First, the modeling was very clear about very large sugarcane yield reductions in Costa Rica while at the same time predicting large global reductions. The net result is a projected increase in area under sugarcane in Costa Rica. Second, coffee production is likely to be greatly affected by climate change in both Costa Rica and around the world, just as with sugarcane. Recommendations are made regarding managing the shift in areas used for coffee growing. Finally, losses in the dairy industry are possible from heat stress if cattle are not sufficiently cooled in the months that are hot and humid, pointing to need for longer-term investments in buildings and cooling equipment that may make a huge difference in future productivity.